THE IMPACT OF PEDAGOGICAL IMAGE ON THE LEARNING PROCESS: PSYCHOLOGICAL AND METHODOLOGICAL APPROACHES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article analyzes the impact of the concept of pedagogical image on the educational process, examining its psychological and methodological aspects. Pedagogical image is a crucial factor associated with a teacher's personal qualities, pedagogical competencies, and methodological approaches. The research findings reveal the influence of pedagogical image on the effectiveness of education and highlight the necessary methods for its development.